Socialization of Legal Understanding Towards Street Merchants (PKL) who Provide Trading in Locations that are Prohibited from A Progressive Law Enforcement Perspective in Kupal Village District. South Halmahera - Muhammad Amin Hanafi; A Amriyanto (Universitas Muhammadiyah Surakarta, 2023)
Although it is not like big cities in Indonesia where the control of street vendors (PKL) is widely highlighted by the local government to maintain cleanliness and public order, in Kupal Village City, Kab. South Halmahera should start taking into account the existence of street vendors (PKL). For this reason, it is very important to regulate, structure and enforce the law for street vendors (PKL) so that there is order and firmness in its implementation. The aim of this research is to analyze the regulation of street vendors in Kupal Village. The activity implementation method consists of three stages. The first preparation stage includes pre-survey, team formation, making and submitting proposals, coordinating teams and partners as well as preparing training tools and materials. The second stage is the program implementation stage in the form of socialization. Socialization is carried out through counseling (presentation of material) and discussions. The third stage is the evaluation and reporting stage. Evaluation is carried out by comparing the conditions of partners before and after program implementation using interview and observation methods. After that, a report is prepared for subsequent publication. The output target in this socialization is to increase understanding of community law regarding street vendors (PKL) who sell in locations that are prohibited from the perspective of progressive law enforcement in Kupal Village, Kab. South Halmahera.